Students Mathematical Creative Thinking and Learning Obstacles in Solving Ill-Structured Exponential Problems - Tsania Rahmatin; Jarnawi Afgani Dahlan; Al Jupri (Universitas Syiah Kuala, 2025)
Mathematics, essential for fostering problem-solving skills, plays a critical role in education. However, the lack of creativity and flexibility among students in solving complex problems like ill-structured problems (ISPs) in exponential material indicates significant learning obstacles. This study aimed to identify and analyze the learning obstacles faced by senior high school students and explore their creative mathematical thinking abilities when addressing ISPs in exponents. Employing a qualitative descriptive method with a Didactical Design Research (DDR) framework, data were gathered through tests, observations, and semi-structured interviews. The study involved 40 purposively selected tenth-grade students from Bandung. Findings reveal that students excel in fluency but struggle with flexibility and originality. Learning obstacles include ontogenic (limited conceptual understanding), didactic (restricted instructional variety), and epistemological (context-dependent reasoning). These obstacles impede students' creative thinking development, especially in producing unique solutions and utilizing alternative approaches. The study concludes that addressing these obstacles requires innovative teaching strategies, such as problem-based learning and didactical designs emphasizing exploration and creativity. These strategies can enhance creative thinking in mathematics, benefiting students' adaptability in academic and real-world challenges. Future research should focus on implementing and refining such designs across various mathematical topics.